The Effects of Weft Density, Weft Yarn Count and Weave Type on Air and Water Vapor Permeability in 100% Acrylic Woven Fabrics - Arzu YAVAŞCAOĞLU; Recep EREN; Gülcan SÜLE (Gazi Üniversitesi Fen Bilimleri Dergisi, 2019)
In this study, the effects of weft yarn count, weft density and weave type on the air and water vapor permeability properties of 100% acrylic woven fabrics were examined and evaluated statistically. Fabrics were produced with two different weft yarn counts (Ne 20/1 and Ne 16/1), three different weft densities (13, 15 and 17 thread/cm) and three different weave types (plain, twill and satin). The results of the study were statistically evaluated by using Mann Whitney U and Kruskal Wallis H tests in SPSS 21 statistics program. According to the result of the study, the air permeability and water vapor permeability decreased when weft density was increased. Air permeability values of fabrics woven with plain weave were lower than those of satin and twill weaves. Greater water vapor permeability values were obtained in fabrics woven with thick weft yarns.